Urgensi Bimbingan Konseling Islam dalam Pendidikan (The Urgency of Islamic Counseling Guidance in Education) - Himam, Muhammad Rofiul; Hidayah, Rifa (Happiness: Journal of Psychology and Islamic Science, 2025)
Education has a very vital role in a person's life. He determines and guides the future and direction of a person's life. Even though there are differences in views among society, education is still considered a primary human need. A person's talents and skills can be developed and honed through the educational process. Generally, education level is also used as an indicator of a person's quality. Education includes the process of guiding individuals physically and spiritually towards the formation of a quality personality. In the Islamic context, education has the meaning of a guide to spiritual and physical growth according to Islamic teachings by wisely directing, teaching, training, nurturing and supervising the application of all Islamic values. In this framework, the role of Islamic guidance and counseling in education is an effort to help individuals grow as human beings who develop in the educational aspect, forming a personality that is useful in life with various insights, views, interpretations, choices, adjustments and skills that suit themselves and the environment. Therefore, the importance of Islamic guidance and counseling is emphasized to achieve development and optimization in the educational process.